PENGARUH SANKSI PERPAJAKAN, TINGKAT PENGHASILAN DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN TAHUN PEMBINAAN WAJIB PAJAK (TPWP) SEBAGAI VARIABEL MODERATING (Studi Empiris UMKM Di Kota Semarang) - Dewi Gayatri Mandasari, 12.05.52.0229; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2016)
This research aims to analyze program TPWP on tax compliance in Dinas Koperasi & UMKM Semarang. The population in this study are personal tax payers UMKM owners registered at Dinas Koperasi & UMKM Semarang. Sampling was done by using convenience sampling method and sample size of 107 respondens. The primary data using multiple liniear regression model. The results showed that the tax penalties and significant positive effect on tax compliance. Income levels and no significant negative effect on tax compliance. The education level of positive and significant impact on tax compliance. TPWP positive and significant impact on tax compliance.TPWP moderate the relationship sanctions and compliance with positive direction and significant meaning to their TPWP able to improve tax compliance.  Keywords: Tax Compliance, Tax Penalties, income Level, Education Level, TPWP